Arthroscopy and Micronized Allogenic Cartilage Matrix Grafting for a Missed Talus Nonunion: A Case Report. Issue 1 (January 2022) - Mathew, Justin; Mahjoub, Adel; Freeland, Erik
Abstract : Case: A 33-year-old man who had experienced polytraumatic injury from a motorcycle collision 5 months previously presented to the clinic with right ankle pain. On physical examination, anterior ankle tenderness was present, and imaging revealed a previously unrecognized nondisplaced talar body fracture with a chondral defect. The patient underwent arthroscopy of the right ankle, which influenced the senior author to perform a medial malleolar osteotomy and subsequent open reduction internal fixation with micronized allogenic cartilage matrix. Conclusion: Arthroscopy provides valuable information for the surgical planning of talar nonunions, and allogenic cartilage matrix graft may provide benefit with associated chondral defects.